Synthesis, characterization, and dielectric properties of polymers functionalized with coumarone and diethanolamine - Bezgin, Feride; Ayaz, Nursel; Demirelli, Kadir (Wiley, 2015)
A series polymers of the poly(4-{[bis(2-hydroxyethyl)amino]methyl}-2-oxo-2H-chromen-7-yl-2-methylpropanoate), P(CIMMAOC)-DEA, were synthesized by modification of poly(4-(chloromethyl)-2-oxo-2H-chromen-7-yl-2-ethylpropanoate), P(CIMMAOC), with diethanolamine (DEA). All polymers were structurally characterized by FTIR, H-1 NMR, UV-vis, and Fluorescence spectra. The electronic features of the polymer, such as lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energies and electrostatic potential (ESP), and the vibrational frequencies were computed by the Becke3-Lee-Yang-Parr (B3LYP) functional using 3-21G* basis set. Dielectric measurements for P(CIMMAOC) and P(CIMMAOC)-DEA were performed by means of an impedance analyzer as a function of frequency and temperature. It was found that the dielectric constant values decreased in the applied frequency range. The values of dielectric constant increased with a rise in concentrations of DEA in polymer for all temperatures. Dielectric constants of P(CIMMAOC) and P(CIMMAOC)-DEA (60%) were calculated as 3.93 and 12.29 at 1 kHz, respectively. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42164.
Keywords: dielectric properties; functionalization of polymers; properties and characterization; spectroscopy; theory and modeling